Providing information support to the Policy Studies Program of the College of Public Administration, University of the Philippines - Lacson, Zenaida C., 1949-
1) Presentation of the aims and objectives of the Policy Studies Program of the U.S. College of Public Administration, with brief discussion of its components; curricular development, policy research, build-up of library collections, and faculty and staff development.